Clinical Lesions in Parvo Virus Infected Puppies - Anilkumar Tangolli, Abhishek; Kumar Gowdaiahnadoddi Krishnaiah, Chetan; Manepanda Appaiah, Kshama (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine parvo virus (CPV) causes acute gastroenteritis in young puppies leading to profuse diarrhoea and vomiting, severe dehydration/ hypovolemia, metabolic acidosis (or alkalosis), bacterial translocation with septicaemia and endotoxemia, systemic inflammatory response syndrome (SIRS), hypercoagulability, multiorgan dysfunction, and death. CPV invades many of the internal organs such as intestinal epithelia, bone marrow, tongue, oral cavity, heart, lung, spleen, liver, kidneys and skin. In PCR positive puppies, petechial haemorrhages were observed along the tip of the eyelids, along the tip line of the lips, around the inguinal region in male puppies, around perineal region in both male and females. These lesions were focal as a single and cluster like appearance.